The effect of environment on intestinal microbial diversity of Panthera animals may exceed genetic relationship - Chen, Lei; Xu, Di; Sun, Mengyao; Li, Ying; Wang, Shen; Gao, Ying; Gao, Zenghao; Shi, Yuying (Frontiers in Microbiology, 2022)
Intestinal microbes are important symbiotes in the gastrointestinal tract of mammals, which are affected by food, environment, climate, genetics and other factors. The gut microbiota of felines have been partially studied, but a comprehensive comparison of the gut microbiota of Panthera species was less reported. In this study, we compared the gut microbial composition and diversity of five species of Panthera (Panthera tigris, Panthera leo, Panthera onca, Panthera pardus, Panthera uncia) by 16S rRNA amplicon sequencing. The results showed that Firmicutes was the most abundant phylum among all Panthera species, followed by Actinobacteria, Fusobacteria, Bacteroidetes, Proteobacteria, Acidobacteria, Verrucomicrobia, Gemmatimonadetes and Euryarchaeota. There were significant differences in observed species of fecal microbiota among different Panthera animals (P < 0.05), indicating that there are species specificity among Panthera fecal microbiota. When the samples were further grouped according to sampling locations, the comparison of alpha diversity index between groups and beta diversity analysis showed that there were significant differences in the fecal microflora of animals from different sampling locations. Cluster analysis showed that fecal microbes of animals from the same sampling location was clustered while gut microbes of animals of the same species but from different sampling locations were separated. These results indicate that environment may have more influence on mammals’ fecal microbial diversity than genetic relationship.